IMPLEMENTASI METODE SYAWIR DALAM MENINGKATKAN PEMAHAMAN SANTRI PADA KITAB FATHUL QORIB DI MADRASAH DINIYAH PONDOK PESANTREN AL-ITTIHAD BELUNG PONCOKUSUMO MALANG - Khofifatul Lathifiyah; Khisna Azizah (Journal Islamic Studies, 2024)
The teacher's method in conveying learning to students is by choosing a method that makes it easier for students to understand the lesson being delivered, therefore the teacher chooses the syawir method in which there is deliberation in the method that makes students active in learning so that students are happy in learning and easily understand lessons. This study has the following objectives: To find out the implementation of the syawir method in increasing students' understanding of the Book of Fathul Qorib at Madrasah Diniyah Pondok Pesantren Al-Ittihad and to describe the results of implementing the syawir method in increasing students' understanding of the Book of Fathul Qorib at Madrasah Diniyah Pondok Pesantren Al-Ittihad. This type of research uses a qualitative approach with a case study type. The data collection techniques are: interviews, observation, documentation and data analysis. There are 3 data analysis namely: data reduction, data presentation, and conclusion drawing. The results of this study indicate that: the students are enthusiastic in learning and enthusiastic, the knowledge achieved by the students related to understanding fiqh becomes wider, the students easily understand what is being learned, the students' self-confidence increases, the students easily remember the meaning of each word in the book, the students are able to read the book smoothly and correctly, smoothly working on questions during the exam.